GIS-Based Analytical Hierarchy Process Flood Hazard Mapping in Deli Serdang, Indonesia Using Satellite Images - Hafizhahurrahman, Zaidan; Aulia Kamal, Shafnanda (Politeknik Statistika STIS, 2025)
As of the regions with a high frequency and significant impact of flood disasters, Deli Serdang in North Sumatera, Indonesia highly requires spatial-based hazard mapping as a foundation for mitigation efforts. This study aims to map the flood hazard levels by integrating the Analytical Hierarchy Process (AHP) and Geographic Information Systems (GIS). Five parameters were analyzed to construct the model: elevation, slope, rainfall, Normalized Difference Vegetation Index (NDVI), and Normalized Difference Built-up Index (NDBI), with data acquired through the Google Earth Engine platform. The AHP weighting results indicate that rainfall is the most dominant factor (40%) influencing the hazard level. The resulting hazard map identifies a clear spatial pattern with a north-to-south gradation, where 50.17% of the total area falls into the high-hazard category, 47.57% into the moderate category, and the remainder into the low-hazard category. A significant finding reveals that all sub-districts within the study area are classified as either moderate or high hazard, confirming the northern coastal zone as the most critical area. The results of this research can serve as a scientific basis for local government in formulating more adaptive and targeted disaster mitigation policies and spatial planning.